IMPLEMENTASI METODE SIMPLEKS UNTUK OPTIMASI KEUNTUNGAN UMKM KULINER: STUDI KASUS UMKM BASO PENTOL MAMAT - Cindy Sulistiawati; Ribi Anggraini, Dhandy Hendra Pratama, Paduloh (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to implement the Simplex method in order to optimize profits in Micro, Small and Medium Enterprises in the culinary sector. Culinary often face challenges in managing limited resources, such as raw materials, labor and production time, which can affect their profit potential. The Simplex Method, which is a technique in linear programming for solving optimization problems, is applied to determine the best combination of resource use and production allocation to maximize profits. This research involves analysis of relevant production and cost data, as well as the formulation of the problem as a linear program. The research results show that the application of the Simplex method can provide an optimal solution in allocating resources to maximize profits by considering existing limitations. Apart from that, this research also provides strategy recommendations to improve operational efficiency and culinary competitiveness of MSMEs. Thus, the Simplex method has proven to be effective as a decision making tool for culinary MSME managers to achieve more optimal and sustainable results.